Damage Assessment and Recovery of Concrete Bearing Capacity After FireExposure: A Systematic Review of the Literature. - Saucedo Segovia, Kleiner Esmit (2025)
This article presents a comparative analysis of various studies focused on concrete performance at high temperatures, particularly considering the degradation and possible recovery of its structural capacity after a fire. Studies are examined that address variables such as the type of concrete used, the incorporation of metallic or synthetic fibers, the addition of pozzolanic materials, the cooling methods applied, and post-fire diagnostic techniques. The reviewed findings indicate that the use of steel or glass fibers can contribute to improving the thermal stability of concrete, although their effectiveness depends on the type of mix and the thermal conditions achieved. Similarly, the incorporation of fly ash has shown positive effects on the residual strength of self-compacting concrete. Both experimental approaches and theoretical models are included, allowing for the assessment of thermal damage and phenomena such as spalling. This review identifies recurring patterns, methodological contradictions, and knowledge gaps, highlighting the need for unified criteria for post-fire structural assessment. Overall, the value of integrating this knowledge into the design and recovery of fire-damaged structures is highlighted.